First records of Asbestopluma hypogea Vacelet and Boury-Esnault, 1996 (Porifera, Demospongiae Cladorhizidae) on seamounts and in bathyal settings of the Mediterranean Sea - Aguilar, Ricardo; Correa, Matthias López; Calcinai, Barbara; Pastor, Xavier; de La Torriente, Ana; Garcia, Silvia (Zootaxa, 2011)
The carnivorous sponge Asbestopluma hypogea, was known only from shallow submarine caves (-15 to -26 m) in the Western Mediterranean Sea and the Adriatic. Herein A. hypogea is reported from outside of caves, on seamounts in the Alboran Sea (-167 m), off the Balearics (-100 m) and north off Sicily (-660 m), and along steep bathyal escarpments in the Strait of Sicily (~700 m). These deeper ROV-based findings of A. hypogea are conform to the typical deep-sea occurrence of the Cladorhizidae.